Assessing access to care for transgender and gender nonconforming people: A consideration of diversity in combating discrimination - Cruz, Taylor M. (Social science & medicine (1982), 2014)
Transgender and gender nonconforming people face stigma and discrimination from a wide variety of sources and through numerous social realms. Stigma and discrimination originating from biomedicine and health care provision may impact this group's access to primary care. Such stigma and discrimination may originate not only from direct events and past negative experiences, but also through medicine's role in providing treatments of transitioning, the development of formal diagnoses to provide access to such treatments, and the medical language used to describe this diverse group. This paper examines the postponement of primary curative care among this marginalized group of people by drawing from the National Transgender Discrimination Survey, one of the largest available datasets for this underserved group. This paper also proposes an innovate categorization system to account for differences in self-conceptualization and identity, which has been of considerable concern for transgender and gender nonconforming communities but remains underexplored in social and health research. Results suggest that experience, identity, state of transition, and disclosure of transgender or gender nonconforming status are associated with postponement due to discrimination. Other findings suggest that postponement associated with primary place of seeking care and health insurance has ties to both discrimination and affordability. These findings highlight the importance of combating stigma and discrimination generated from within or experienced at sites of biomedicine or health care provision in improving access to care for this group of people. Improving access to care for all gender variant people requires a critical evaluation of existing research practices and health care provision to ensure that care is tailored as needed to each person's perspective in relation to larger social processes. •Transgender/gender-nonconforming individuals postpone seeking care at high rates.•Different predictors are associated with different reasons for postponement.•Use of broad gender categories masks considerable differences among this population.•Diversity among this population needs to be taken into account in future research.